ANALISIS KUALITAS WEBSITE E-COMMERCE SHOPEE TERHADAP KEPUASAN PENGGUNA MENGGUNAKAN METODE WEBQUAL 4.0 - Adhita Arif Setyawan; Arif Setiawan (POLITEKNIK PIKSI GANESHA, 2023)
The development of online stores is currently greatly increasing. This can be seen from the increasing number of local and international online store service providers that have sprung up, making competition even more competitive. The development of online stores is supported by developments in information technology and unlimited use of the internet. This has an influence on the behavior of consumers who want fast and accurate information. The quality of a website can be measured through three dimensions of quality, namely the quality of ease of operation for users which includes easy to understand, browse, use, and attractive. Then the quality of the information conveyed includes information that is accurate, reliable, up to date, according to the topic of discussion and details. The last is the quality of interaction which includes providing a sense of security when consumers make transactions, being able to provide convenience in communicating with fellow users, having trust in storing consumer personal information and creating a specific community. Now with so many online sales, many websites compete by providing an attractive appearance on the website, providing accurate service and information so that users don't hesitate in making transactions. Based on the background above, the authors propose a study entitled